Simulating cave growth, primary fragmentation and flow using a mesh-free approach - Thanh Le, V.; Viet Nguyen, T.; Karakus, M.; Nguyen, G.D.; Chester, C.; Musolino, M.; Hang Bui, H. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Block-and-panel caving operations rely on the controlled propagation of rock mass failure. However, the mechanisms governing cave advance, fragmentation and stability remain unclear. Observations from physical modelling and field studies indicate that cave growth may occur through either gradual damage accumulation or discrete fracture banding. However, a unified numerical explanation of these behaviours is still limited. This paper applies a mechanical smoothed particle hydrodynamics (SPH) modelling approach with an energyregularised damage-plasticity constitutive model to simulate the complete rock caving process. The approach enables continuous representation of fracture initiation, progressive fragmentation and gravity-driven material flow, while accounting for stress path–dependent failure under both compressive and tensile loading conditions. Numerical simulations of centrifuge-scale caving experiments successfully reproduce key caving features observed in practice, including stepped cave advance via parallel fracture bands, transient arching, airgap formation and eventual roof collapse. The results demonstrate that fracture banding emerges from the interaction between undercut geometry, loss of confinement and stress path transitions during cave propagation. Parametric analyses indicate that the draw/undercut schedule primarily controls early-stage cave development by controlling the spatial-temporal pattern of support removal and stress redistribution, thereby promoting either a continuous cave back or spatially concentrated cave growth above isolated undercut zones. In parallel, the initial dilation angle, , provides a strong constitutive control on caveability: lower values favour progressive banded failure, whereas higher values promote stable arching and delayed cave advance. The modelling results provide mechanistic insight into cave propagation and stability and demonstrate the capability of the SPH-damage-plasticity approach to capture fracture development, primary fragmentation/material detachment, and post-failure flow in a single mesh-free simulation.